Postoperative pulmonary calcification in a child with truncus arteriosus. (2nd May 2013) - Morrison, Margaret Louise; Casey, Frank; Paterson, Annie; Shields, Mike
Abstract : Pulmonary calcification is uncommon in children. It is rarely described following cardiac surgery. Here, the authors describe the case of an infant who developed extensive pulmonary calcification following the repair of truncus arteriosus.